-(5)/(9)x+3x-3(1)/(3)=(2)/(9)

Simple and best practice solution for -(5)/(9)x+3x-3(1)/(3)=(2)/(9) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(5)/(9)x+3x-3(1)/(3)=(2)/(9) equation:



-(5)/(9)x+3x-3(1)/(3)=(2)/(9)
We move all terms to the left:
-(5)/(9)x+3x-3(1)/(3)-((2)/(9))=0
Domain of the equation: 9x!=0
x!=0/9
x!=0
x∈R
We add all the numbers together, and all the variables
-5/9x+3x-31/3-(+2/9)=0
We add all the numbers together, and all the variables
3x-5/9x-31/3-(+2/9)=0
We get rid of parentheses
3x-5/9x-31/3-2/9=0
We calculate fractions
There is no solution for this equation

See similar equations:

| 5k+k+4-1=2k+4k+4 | | 2n-7=1/2 | | -2,500h-3000+500h+1000=-36,000 | | 2.7x+8.3x=44 | | 36x18=x | | 6=x/5-7 | | -7x+2x=30 | | 90=5f | | 5+e=-10 | | 8m+7m+7=3(5m-8) | | x+12.66=18 | | (x-3)+3=10 | | 1/2(10k-16)+11=4K+8 | | 43+(3x+18)+(6x-16)=180 | | 20=4+w | | -5w+4=-31 | | 21-4x=11 | | 3/4y-2/3=4/6 | | (5x^2)=45 | | t+1.6=4 | | (z+4)=79 | | 17-n+11=13-4n | | 22x-7-9x+11=-3(-2x+3)-1+6x | | 4(2x-6)=2x+7 | | 7/(x−5)=6 | | 2x2=182 | | 5x-38=18 | | 8/20=x/10 | | -10=x/4+6 | | 8÷n=4 | | 8x+14+4x-8+70=180 | | (4x+6)=46 |

Equations solver categories